In-House Style in Commercial Publishing Industries - Grace Effiong ETUKUDO; Luqman Ayanlola ATANDA; Etido Sunday UDOEDUOK (European Science Publishing, 2023)
This work was discussed about publishing industries. It gives the details about the requirements that brings publishing into existence. Also discussed about how publishing emanated. Publishing house style was also discussed to know different kinds of styles to be adopted to the success of the publishing industries.
Keywords: in-house, style, commercial, publishing, industries.